The hiding place - Ten Boom, Corrie; Sherrill, Elizabeth; Sherrill, John L. (Hendrickson classic biographies., 2015)
An old Dutch watchmaker and his two daughters become the center of a major underground operation: to hide Jewish refugees from the occupying Germans. They break all the rules to save the lives of men, women, and children being hunted by the Nazis. The cost of their bravery is betrayal, and they end up in the dreaded Ravensbruck concentration camp. Nevertheless, they continue their efforts to save those around them.